Limb-Girdle Muscular Dystrophies - J Gordon Millichap (Pediatric Neurology Briefs, 2003)
The phenotype in limb-girdle muscular dystrophy (LGMD) type 21 was defined by mutation analysis, protein studies, and respiratory and cardiac involvement studied in 16 patients from 14 families with fukutin-related protein (FKRP) gene mutations and LGMD, at the Institute of Human Genetics, University Newcastle upon Tyne, UK.